2020
DOI: 10.1016/j.colsurfb.2019.110597
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically-oriented type I collagen-SiO2@Fe3O4 rods composite hydrogels tuning skin cell growth

Abstract: Conferring orientational order to biological hydrogels constitutes a fruitful strategy for the guided growth of cells. The ability of anisotropic magnetic particles to align along an external magnetic field appears as a particularly, yet poorly explored, strategy to achieve such an orientation in 3D. For this purpose, silica rods coated with magnetite nanoparticles were prepared. When dispersed in a collagen type I solutions, they could be aligned along the magnetic field generated by two plate magnets within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…More recently, Shi et al reported the preparation of anisotropic collagen hydrogels by magnetic field-induced alignment of SiO2@Fe3O4 rods embedded within the pre-gel solution. [18] These authors found changes in the rheological properties of hydrogels connected to rod alignment and, more interestingly, a statistically significant enhancement of cellular activity in anisotropic hydrogels with respect to Fig. 8.…”
Section: Cell Viability Assessmentmentioning
confidence: 84%
See 1 more Smart Citation
“…More recently, Shi et al reported the preparation of anisotropic collagen hydrogels by magnetic field-induced alignment of SiO2@Fe3O4 rods embedded within the pre-gel solution. [18] These authors found changes in the rheological properties of hydrogels connected to rod alignment and, more interestingly, a statistically significant enhancement of cellular activity in anisotropic hydrogels with respect to Fig. 8.…”
Section: Cell Viability Assessmentmentioning
confidence: 84%
“…[15] Our decision to embed magnetic nanoparticles (MNP) within the chosen FAH was based in previous studies that support the hypothesis of improving the mechanical properties of biomaterials containing MNP. [16] Additionally, other advantages have been reported for magnetic hydrogels in the field of tissue engineering, such as the improvement of cell culture efficiency of some types of cells such as fibroblasts [17,18] and the stimulation of adhesion, proliferation, and differentiation of cells in vitro, and even bone formation in vivo [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“… Lyu et al (2021) fabricated flexible ultrasonic patches, in which ultrasound could accelerate the wound healing by activating RAC1 in the dermis and epidermis, thus effectively treating chronic wounds. Shi et al (2020) seeded normal human dermal fibroblasts on an anisotropic magnetic hydrogel, and the cells were oriented to grow under the guidance of the magnetic field, indicating that the anisotropic magnetic hydrogel showed a beneficial effect on the skin tissue regeneration.…”
Section: Functionalization Of Hydrogels For Wound Healingmentioning
confidence: 99%
“…Further, anisotropic magnetic scaffold based on collagen was recently reported to influence skin cells [187]. The author synthesized silica rods functionalized with iron oxide nanoparticles (SiO 2 @Fe 3 O 4 ) and incorporated them into a type I collagen-based hydrogel.…”
Section: Soft Tissue Cellular Response Modulation By Magnetic Scaffoldsmentioning
confidence: 99%